Interrelationship between COVID-19 and diabetes mellitus: a systematic review (Research, Society and Development, 2021)
Introduction: Individuals with diabetes are at a higher risk of hospitalization and mortality from viral, bacterial and fungal infections. Coronavírus-2019 (COVID-19), caused by severe acute respiratory syndrome coronavírus-2 (SARS-CoV-2), spread rapidly to countries and claimed thousands of lives by December 2020. Notably, in several studies, diabetes is one of the most reported comorbidities in patients with severe COVID-19. Objective: Discuss the influence of diabetes on the prognosis of patients with COVID-19 through a literature review. Methodology: It is a systematic review study. To identify the literature published until December 2020, individual search strategies were applied to the following electronic databases: PubMed, Medline, Lilacs and SciELO. Results: It can be noted that based on the new clinical data obtained from COVID-19 patients, several mechanisms, such as cytokine storm, pulmonary and endothelial dysfunction and hypercoagulation, which can make individuals with diabetes more vulnerable to COVID-19. Epidemiological studies show that poorly controlled diabetes is a risk factor for several infectious diseases. Conclusion: Given the clinical importance of diabetes and the pandemic nature of coronaviruses, understanding how diabetes affects the severity of COVID-19 is critical to the development of public awareness and personalized treatment for individuals affected by the disease.